Underwater multilateral tele-operation control with constant time delays. (December 2021) - Mo, Yiting; Song, Aiguo; Wang, Ting
Abstract: In the complex underwater environment, it is difficult to complete teleoperation tasks due to dynamic environments. Through cooperation among manipulators, a multilateral teleoperation system has the potential to achieve better performance than conventional bilateral teleoperation systems. In this paper, we propose a multilateral teleoperation control method that can be easily applied for underwater grasping tasks. Specifically, a new structure involving two (or multiple) masters and a single slave is investigated, which is treated as a linear combination of multiple subsystems under time delays. A control method based on linear matrix inequality exponential convergence and nonlinear disturbance is presented to estimate the model uncertainties of the system and unknown external disturbances during grasping process. The asymptotic stability is analyzed using the established Lyapunov–Krasovskii functional. Numerical simulations and real experiments performed for the task of grasping a plastic foam block are reported to verify the proposed control method in real applications. Graphical abstract: Highlights: A multilateral teleoperation structure and controller is proposed. A control method based on linear matrix inequality (LMI) exponential convergence and nonlinear disturbance is presented based on the proposed structure. The asymptotic stability is analyzed by L–K functional and real experiments are performed to verify the proposed method.